Some of the methods used to solve complete and incomplete differential equations (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper studies the methods used to solve complete and in complete differential equations and types of first order and second order and Exact differential equation to solve integration general in This equation Fur there more, and the Special cases to find the integration factor use solve those types of equations is use as well,supported by a relevant variety of examples.